Research on Multi-criteria Material Selection of Automobile in Full Cycle under the Background of Green Manufacturing. Issue 1 (May 2021) - Ding, Zhensen; Fang, Haifeng; Yao, Zhanhui; Liu, Jinzhou; Wang, Jia
Abstract: Under the background of the continuous strengthening of green manufacturing, the automobile industry, as a typical representative of the industry, will be an important battlefield for the green development of China's industry. In addition, with the emergence of new alternative materials for automobiles, the selection range of materials for automobile parts is gradually expanding. Literature from year 2009 until year 2019 were collected which is focused on related automotive material selection. It's worth noting that the concept of "green manufacturing" was proposed in 2018. It is found that the selection criteria of automobile materials have been expanded from only focusing on mechanical properties to economic performance, technological performance and environmental performance. The multi-attribute material selection method is emerging because of the more complicated material selection caused by the increase of environmental attributes, which also brought manifest divergences in the selection of secondary indicators and the setting of weights. According to the practical application, the optimization measures related on the selection basis of secondary indicators and setting weights from the perspective of producers and consumers in the whole life cycle were proposed.